ARGUMEN FORMALISASI HUKUM EKONOMI SYARIAH - Ahmad Ali MD (Jurnal Dialog, 2013)
This article asserts that Islamic law of economy has a very important position in the national legal system. The Islamic law of economy as part of Islamic law and constitute a solid argument to be used as the basis of national law-making as a whole. The significance of Islamic law of economic is based on historical arguments, sociological, juridical, philosophical, and political. This assertion is refuse whom doubted and looked formalization of Islamic law, particularly the Islamic law of economy, is not important. This conclusion is obtained through alsiyasat al-shar‘iyah and the national legal politics approachs.